A brief review on friction reduction via dimple structure for piston engine. (2018) - Rahman, Haniff Abdul; Ghani, Jaharah A.; Mahmood, Wan Mohd Faizal Wan
Advanced low-friction coatings and surface texturing are potentially new methods for reducing friction in reciprocating engines. The piston is an engine component that can benefit from the introduction of micro dimple texturing on its surface to improve engine efficiency. The design of the piston skirt is one of the key features to be taken into account in controlling the performance of friction, oil consumption and noise. The piston skirt contributes to around 25-47% in piston-cylinder system losses due to engine friction. A micro dimple distribution on the surface will act as an oil reservoir and provide lubrication to reduce friction by up to 30%. In addition, micro dimple texturing is also beneficial in generating hydrodynamic pressure and a load-carrying capacity on sliding surfaces, hence contributing to lower friction. The aspect texture ratio, λ texture density, ρtexture and relative texture depth, S, are some of the important parameters that need to be considered in designing a dimple structure and pattern on a piston skirt surface to optimise the hydrodynamic pressure effect and to reduce friction.